Wacana Pertobatan Muslim Indonesia di Media Digital - Ahmad Zamzamy (LPPM Stikosa - AWS, 2019)
Nowadays, the phenomenon of Hijrah that occurs in digital media. This phenomenon of Hijrah is more widely covered and broadcast by artists and young people. The word “Hijrah” is more often echoed than the word repentance, especially in digital media. Therefore, the question arises of why the discourse of repentance is not used and how the position of the word repentance in digital media. This article is to study “Hijrah”, a word or language that is chosen and used and what it's content. Repentance in this writing only focuses on the scope of Indonesian Muslim circles. Method of this research using discourse media analysis with Foucault's approach. The data collection uses documentation, literature studies, and observations. The results reveal that the word repentance is still used with real understanding. Then came the word Hijrah whose meaning was almost equalized and could be confused with the meaning of the word repentance. The word Hijrah is becoming more popularly used than the word repentance. The word Hijrah appears with a load of interests and is inseparable from power. The choice of the word repentance or the word Hijrah depends on who the user is. Examples of users are from the state or government, the media, industry, the general public, and Islamic groups. Finally, the word Hijrah is more often used than the word repentance in digital media until now.